(untitled) (Revista Latino-Americana de Enfermagem, 2015)
Objective: to determine the prevalence of the types of relations to career - commitment and entrenchment - of nurses from public and private hospitals. Methods: field survey with a quantitative approach. A total of 237 nurses participated in the survey through a questionnaire with 43 questions about sociodemographic data, occupation, and relation to career. Descriptive statistics, frequency analysis, and Mann-Whitney U test were used for data analysis. Results: nurses from public and private hospitals have a high level of career commitment and a median level of career entrenchment. Conclusions: nurses have a stronger relation of affection and identification to career than a relation of stagnation, maintained primarily due to investments, followed by emotional costs and lack of alternatives. This fact is associated with individuals continuing in nursing and having a strong commitment to activities.